Handbook of civil engineering calculations - Hicks, Tyler Gregory (McGraw-Hill handbooks., 2000)
Handle every day-to-day calculation instantly and accurately. Now, a single authoritative reference offers you a surefire way to save time handling routine and non-routine calculations in the design, construction, rehab and maintenance of all types of structures. Edited by Tyler G. Hicks, Handbook of Civil Engineering Calculations explains and illustrates over 500 key calculations covering the entire field: structural steel engineering and design; reinforced and prestressed concrete; timber engineering; soil mechanics; surveying, route design, and highway bridges; fluid mechanics; pumps, piping, and hydro power;water supply and stormwater; sanitary wastewater treatment and control; and engineering economics.Using both customary and SI units, each calculation procedure includes a worked-out example with numbered steps. You see exactly how to compute the desired values for a particular design, and go quickly from data to finished design.